Stellate Cell Activation in Tropical Calcific Pancreatitis Compared to Alcoholic Pancreatitis, Adenocarcinoma of Pancreas and Normal Pancreas - Cyriac, Johny; Mahadevan, Pushpa; Augustine, Philip; Ramesh, Hariharan; Koshy, Abraham (JOP. Journal of the Pancreas, 2012)
<!–[if gte mso 9]> Normal 0 14 false false false <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabella normale"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif] –> Context Pancreatic stellate cell (PSC) is known to be the source of fibrosis in pancreatic pathology of various etiologies. However, there is no published data on activation of PSCs in tropical calcific pancreatitis. Objectives The present study was undertaken to estimate the proportion of activated stellate cells, in a semi-quantitative manner, in normal pancreas and pancreatic fibrosis due to, tropical calcific pancreatitis, alcoholic chronic pancreatitis and pancreatic adenocarcinoma. Patients Surgically resected specimen from patients with tropical calcific pancreatitis (n=22), alcoholic chronic pancreatitis (n=16), adenocarcinoma of pancreas (n=20) and normal pancreas (n=20) were included. Main outcome measures Expression of CD34, and alpha-smooth muscle actin (α-SMA) was assessed by immunohistochemistry. Morphometry was performed by a point counting procedure and CD34 positive areas were excluded from α-SMA positive areas for estimating activated PSCs. Statistics The one-way ANOVA and the Tukey multiple comparison test were used to compare the proportion of activated stellate cells among the four categories. Results In all the disease conditions studied, namely, tropical calcific pancreatitis (16.7±14.5%, mean±SD), alcoholic chronic pancreatitis (13.6±12.4%) and pancreatic adenocarcinoma (22.8±14.4%), there was highly significant (P<0.001) increased percentage of activated PSCs compared to normal pancreas (-0.9±6.4%). Proportion of activated PSCs in tropical calcific pancreatitis was similar to that in cases of alcoholic chronic pancreatitis and pancreatic adenocarcinoma. Such activation is documented for the first time in tropical calcific pancreatitis while it is known for the other causes. Conclusions The present study suggests that a final common pathway of PSC activation leads to fibrogenesis in tropical calcific pancreatitis just as in other pancreatic pathologies. Image: Representative staining pattern observed in cases tropical calcific pancreatitis.